Influence of superplasticizers admixtures in the alkali-silica reaction - Silva, C.F. (2017)
The alkali-silica reaction (ASR) consists of the reactive process in which aggregates containing reactive silica constituents react with alkalis and hydroxyl ions present in cement pore solution. It is suspected that some superplasticizers admixtures can contribute to the increase in concrete alkalinity. Literature presents some contradictory results about its influence on ASR. In this work the influence of superplasticizers admixtures in mortars prepared with pozzolanic admixtures was evaluated by accelerated mortar-bar tests and atomic absorption spectrophotometry. In the pozzolanic mixes the cement was replaced by 15% (weight %) of metakaolin or silica fume. Three superplasticizers admixtures (melamine, lignosulfonate and naphthalene) were utilized in three levels. The results show the mortars with the melamine based superplasticizers presented the lower content of soluble alkali and expansion. It is concluded that this admixture could be the most